(3cTa GdXdGe Yf hLhg TQGFY GdESdGes - (3eMSf Hf eQJVi Hf bGSe, J (B1238 (3g`s ((3eMeO QVG Hf eMeO GdMSfGhjs)
(3ChdgG (B:s
(3cJGH GdUdGI(B: (3hgj dZI deYGf CTgQgG(B...s
(3BNQgG (B:s
(3hgh dG jJWhY HQcYI MJi JbVi GdaQjVI Ydi WQjb GdYehe (B... (3Ch HJbOje GdYeheGJ GdeGfYI dehGabJgG ddCUds
(3GdJhKjbGJ GdeQLYjI (B:s
(3eYLe GdeDdajf(B: (3L(B3(3, U(B22s
(3eYLe GdeDdajf(B: (3L(B3(3, U(B22s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3abg GdePGgH GdCNQis